The role of aspirin in the prevention of ovarian, endometrial and cervical cancers. (October 2020) - Joharatnam-Hogan, Nalinie; Cafferty, Fay H; Macnair, Archie; Ring, Alistair; Langley, Ruth E
Drug repurposing is the application of an existing licenced drug for a new indication and potentially provides a faster and cheaper approach to developing new anti-cancer agents. Gynaecological cancers contribute significantly to the global cancer burden, highlighting the need for low cost, widely accessible therapies. A large body of evidence supports the role of aspirin as an anti-cancer agent, and a number of randomized trials are currently underway aiming to assess the potential benefit of aspirin in the treatment of cancer. This review summarizes the evidence underpinning aspirin use for the prevention of the development and recurrence of gynaecological cancers (ovarian, endometrial and cervical) and potential mechanisms of action.